2016
DOI: 10.1177/0960327116655389
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different scores as predictors of mechanical ventilation in drug overdose patients

Abstract: The decision of intubation and mechanical ventilation in poisoned patients with impaired consciousness can be a difficult task. The present study aimed to evaluate the power of Glasgow Coma Scale (GCS), acute physiology and chronic health evaluation (APACHE II), rapid acute physiology score (RAPS) and rapid emergency medicine score (REMS) at admission in predicting the need of intubation and mechanical ventilation in drug overdose patients with disturbed consciousness level (DCL). This prospective obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
2
8
0
1
Order By: Relevance
“…In the current study, REMS was good predictor for requirement of mechanical ventilation at cut off value > 4. This matches with (Olsson and Lind, 2003), (Goodacre, Turner and Nicholl, 2006), (El-Sarnagawy andHafez, 2017) &(Abd Elghany et al, 2018) who supposed REMS as a valuable scoring system that tends to be a good predictor of morbidity and duration of hospitalization in patients admitted to the Emergency department (ED).…”
Section: Discussionsupporting
confidence: 75%
“…In the current study, REMS was good predictor for requirement of mechanical ventilation at cut off value > 4. This matches with (Olsson and Lind, 2003), (Goodacre, Turner and Nicholl, 2006), (El-Sarnagawy andHafez, 2017) &(Abd Elghany et al, 2018) who supposed REMS as a valuable scoring system that tends to be a good predictor of morbidity and duration of hospitalization in patients admitted to the Emergency department (ED).…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, Maignan et al 52 verified that GCS was the only clinical parameter associated with ICU admission in patients with deliberate drug poisoning who presented with slight symptoms on admission. El‐Sarnagawy and Hafez 53 also identified GCS of ≤8 on admission as the most sensitive (100%) predictor for mechanical ventilation in drug‐overdosed patients. Moreover, many studies demonstrated the prognostic value of the GCS, heart rate, SBP, and respiratory rate in predicting outcomes of the ICU admitted poisoned patients 16,29,54 …”
Section: Discussionmentioning
confidence: 97%
“…The three studied scores were evaluated as predictors of the need for ICU admission and/ or MV in different poisoning cases but not TCAs. El-Sarnagawy and Hafez (2017) and Shahin and Hafez (2020) found that APACHE II score and REMS were good predictors for the need of MV in overdosed cases with disturbed consciousness and in cases with anticholinesterase inhibitors (AChEIs) poisoning. Abd Elnoor et al (2019) concluded that PSS and APACHE II score are good predictors for the need of ICU admission in aluminum phosphide and digitalis poisoning cases.…”
Section: Discussionmentioning
confidence: 99%